Low Teenager Participation in Religious Activities: Analysis of Inhibiting Factors and Implications for Development - Usrijal Usrijal; Aidil Saputra; Banta Ali (ISTIFHAM, 2025)
The transformation of information landscapes and digital culture has significantly influenced youth participation in religious activities in Leuhan Village, Johan Pahlawan District. This study aims to analyse the forms of youth involvement in religious programs (such as majelis taklim, sermons, Maulid celebrations, and Dalail Khairat), identify internal and external inhibiting factors, and formulate participatory and contextual strategies for religious development. A qualitative approach was employed through interviews and observations, with data analysed using Miles & Huberman's model (data reduction, presentation, and verification) to ensure consistency with field evidence. The findings indicate that youth involvement remains low, sporadic, and limited to technical roles, thereby failing to strengthen religious knowledge and internalise values. Inhibiting factors include weak personal motivation, lack of family support, peer influence, dominance of social media, and religious program designs that are less participatory and not youth-friendly. This study recommends more innovative and participatory development strategies, such as reformulating activities to be more interactive, involving youth in strategic roles, strengthening religious peer networks, and fostering synergy between families, mosques, and communities. This approach is expected to increase interest, sense of belonging, and commitment to religious values among youth, enabling them to remain steadfast in facing the challenges of the digital era.